Competition of pricing of essential inputs: The case of access charges for the use of the Italian rail infrastucture - Ugo Arrigo; Giacomo Di Foggia (UTMS Journal of Economics, 2013)
This paper explores the access charge for the use of the Italian rail infrastructure. Access problems arise when the provision of a complete service to end users requires the combination of two or more inputs, one of which is non-competitive (OECD, 2004). It is a well-known fact that excessive access charges mean higher prices for rail passengers and rail freight companies when using the infrastructure. We conclude that the structure of the access charge has changed significantly with the recent introduction of the HS/HC (high-speed and high-capacity) network; specifically, the fixed component has lost importance, whilst the variable component reaches 94%. The results of this paper provide evidence of the access charge for HS/HC being above 13 exteuro/km.
Keywords: L13; L52; L92; 330; railway; competition; access charge; Italy; regulation; high-speed